Development Of Canva-Assisted Interactive Learning Media To Improve The Critical Thinking Skills Of Elementary School Students In Science And Science Subjects - Dwi Fajariyanto, Septian; Firdaus, Fery Muhammad; Nirmala, Sri Dewi (Jurnal Pendidikan dan Pengajaran Guru Sekolah Dasar (JPPGuseda), 2025)
This research aims to develop Canva-assisted interactive learning media designed to improve the critical thinking skills of elementary school students through a differentiated learning approach. This media was developed using a 4D model (Define, Design, Develop, Disseminate) and was piloted on grade V students in Cluster 3 Banyuresmi, Cigudeg District, Bogor Regency. The results of the study show that this media is very feasible to use with a feasibility score of 91.4% for the media aspect, 91.25% for the material aspect, and 97.22% for the language aspect. The level of practicality reached 96.77%, indicating that this media is easy to use by teachers and students. In terms of effectiveness, this media has been proven to improve students' critical thinking skills with an average N-Gain of 0.57 (quite effective category). With features such as visual presentations, interactive quizzes, and infographics, this medium motivates students to be actively engaged in learning and supports a variety of learning styles, such as visual, auditory, and kinesthetic. This study concludes that Canva-assisted learning media can be used as an innovative solution to improve the quality of learning in elementary schools.